Status, happiness, and relative income - John Beath; Felix R. FitzRoy (Institute for the Study of Labor (IZA), 2007)
Models of status based on Frank's (1985) count of the number of people with lower conspicuous consumption are inconsistent with the extensive empirical literature on happiness and well-being. The alternative approach to consumption interaction which uses some form of relative income has been developed in various contexts. These predict that a representative agent's well-being will increase with real income or consumption. However, this is again inconsistent with the time-series evidence for advanced economies. In this paper we combine a simple model of relative income with a distribution of ability that correctly predicts both time series results of near constant utility, and the positive, concave cross-sectional relation between income, working time and happiness
urn:nbn:de:101:1-20080415176
Keywords: 330; Sozialer Status; Einkommenshypothese; Lebenszufriedenheit; Großbritannien; USA